SYNTHETIC BIOLOGY-DRIVEN BIOPLASTICS: A LIFE CYCLE ASSESSMENT AND ENVIRONMENTAL IMPACT STUDY - Azhar, Ardi Azhar; Alves, Livia; Gomez, Raul (Yayasan Adra Karima Hubbi, 2025)
The pervasive environmental pollution caused by petroleum-based plastics has catalyzed the search for sustainable alternatives. Bioplastics, derived from renewable biomass, offer a promising solution, yet their production can be inefficient and compete with food resources. Synthetic biology provides powerful tools to engineer microorganisms for the high-yield production of bioplastics like polyhydroxyalkanoates (PHA) from non-food feedstocks. This study aimed to conduct a comprehensive life cycle assessment (LCA) to quantify and compare the environmental impacts of PHA produced via a synthetically engineered microbial platform against conventional polyethylene terephthalate (PET). A